KONJUNGSI DALAM LIRIK LAGU-LAGU MR. BIG PADA ALBUM â€œWHAT IFâ€ - KODONG, GARVIN (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research entitled â€œ Conjungtions in the lyrics of the songs of Mr. Bigâ€ describes theÂ  conjuctions found in the songs of the album â€œWhat Ifâ€ ofÂ  group bandÂ  called Mr. Big. Conjuctions are function words that have grammatical functions that are used to connect words, phrase, clause and sentences .The conventional types of these connectiveÂ  words are coordinate conjuctions and subordinate conjuctions The objective of this study is to identify, analyse and describe the conjuctionsÂ  in the songs of Mr. Big and the method used in this research is descriptiveÂ  The concepts used in analysed the conjuctions followsÂ  Payne (2011), Quirk and Greenbaum (1999). The resultÂ  shows that theÂ  conjuctions found in the lyrics of the songs of Mr.Big are: corrdinate conjuctions and . but, or,Â  and for, and subordinate conjuctions are where, when, that, after, how, what, as far as, since, cause.Â Â Â Â  The function of the coordinate conjunctions is to connect words, phrases, clauses and sentences, whereasÂ  the subordinate conjunctions is to connect clauses. It is expected that this research is to support the concept of conjunctions in English as well as be beneficial to increase studentsâ€™ knowledge on conjunctions and in understanding more the songs of Mr. Big. The meaning of these conjunctions are as the meaning stated in the concepts used. Key words: conjunctions, coordinate and subordinate conjunctions, songs, Mr. Big